Taking Form, Making Worlds: Cartonera Publishers in Latin America. - Proenza, Diana (Papers of the Bibliographical Society of America, 2025)
The article focuses on "Taking Form, Making Worlds," a book that explores cartonera publishing, a Latin American practice of creating collaboratively hand-painted books from recycled cardboard. Authors Lucy Bell, Alex Ungprateeb Flynn, and Patrick O'Hare examine cartonera as an intersectional, decolonial movement that emphasizes environmental, Indigenous linguistic, and labor justice, drawing on research from Mexico, Brazil, and Argentina. The book details the history, methodologies, and diverse practices of cartonera, highlighting its role in uplifting marginalized voices and fostering community engagement through workshops, exhibitions, and collaborative projects. It serves as a comprehensive survey of cartonera's pluriversal nature and proposes a transformative model for bibliographical research that encourages mutual collaboration among scholars and practitioners.